Survival Rate of Barramundi (Lates calcarifer) Larvae Maintenance at Balai Besar Riset Budidaya Laut dan Penyuluhan Perikanan (BBRBLPP) Gondol - Humaero, Nanda Wahyuni Al; Diniariwisan, Damai (Aquaculture Department, University of Mataram, 2025)
Barramundi (Lates calcarifer) is a high economic commodity that has euryhaline properties. The maintenance of barramundi larvae is quite crucial in its cultivation efforts. This study aims to determine the survival rate of barramundi during maintenance at the Balai Besar Riset Budidaya Laut dan Penyuluhan Perikanan (BBRBLPP) Gondol, Bali. The activity lasted for 35 days, observing the parameters of larvae development, type and variety of feed, and water quality. The feed used consisted of natural feed such as Rotifera sp., Nanochloropsis sp., and Artemia sp., as well as artificial feed in the form of PSP and KAIO 3. Feeding was carried out gradually according to the age of larvae with adjusted frequencies and doses. The results showed that larvae showed progressive morphological and behavioral development from day 0 to day 27. The survival rate achieved was 79% of the total 40,000 larvae released, far exceeding the SNI standard (20%). Water quality during maintenance was within the optimal range. Additional efforts such as adding probiotic, daily siphoning, and water changes contributed to successful rearing. These results demonstrate that the combination of good feed and optimal water quality management significantly influences the success of barramundi larval cultivation. This study provides an important foundation for the development of efficient and sustainable large-scale barramundi cultivation.